Metaphylactic effect of calcium on milk composition and animal health in post-partum dairy cows - ALBANI,KÁSSIO D. (2019)
Abstract: The aim of this study was to evaluate the effects of subcutaneous calcium administration in post-partum dairy cows with respect to carbohydrate, protein and lipids metabolism, as well as its effects on milk composition. Twenty post-partum dairy cows were randomly divided into two groups (n=10): a control and a treated group with a single dose (150 mL) of calcium. Blood collection was performed on post-partum days 1, 2, 3, 7 and 10. In addition, we measured serum levels of total calcium, total proteins, albumin, globulins, glucose, cholesterol, triglycerides, as well as creatine kinase (CK) activity. We determined milk composition on post-partum days 5, 10 and 20. Serum total calcium levels was higher on post-partum days 3 and 7 in the treated group. Serum urea (day 3) and triglycerides (days 7 and 10) levels were higher in the treated group, as were CK activity levels at post-partum days 2 and 3. Serum glucose and cholesterol levels were lower on post-partum day 2 in treated animals. Fat (day 20) and lactose (day 10) content in milk samples were higher than in the treated animals. We concluded that treatment with calcium in cows during the post-partum period changes biochemical variables related to metabolism.